1987
DOI: 10.1002/hon.2900050103
|View full text |Cite
|
Sign up to set email alerts
|

Purine degradative enzymes in circulating malignant cells of patients with chronic B cell neoplasia

Abstract: Previous reports have shown that the purine degradative enzymes adenosine deaminase (ADA), purine nucleoside phosphorylase (PNP) and ecto-5'-nucleotidase (5'NT), play an important role in the normal development of lymphocytes and that investigations of these enzymes are of value in defining subsets of lymphoid malignancies of T-cell origin. Pharmacological inhibition of one of these enzymes has been found to be an effective treatment for a few lymphatic neoplasia. We have studied the activities of the above en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…For each of these stages a precise level of ADA and 5'-nucleotidase, among other enzymes, occurs [25]. It is clear, not only for T cell-derived leukaemias but for most types of haematological malignancies, that the level of purine degradative enzymes is useful for the diagnosis and/or prognosis of the disease [1,[26][27][28]. Finally, an interesting possibility that should be further explored is that purine metabolizing enzymes present on the surface of the cells may be important accessory molecules for cell triggering.…”
Section: Resultsmentioning
confidence: 99%
“…For each of these stages a precise level of ADA and 5'-nucleotidase, among other enzymes, occurs [25]. It is clear, not only for T cell-derived leukaemias but for most types of haematological malignancies, that the level of purine degradative enzymes is useful for the diagnosis and/or prognosis of the disease [1,[26][27][28]. Finally, an interesting possibility that should be further explored is that purine metabolizing enzymes present on the surface of the cells may be important accessory molecules for cell triggering.…”
Section: Resultsmentioning
confidence: 99%
“…These studies showed very low levels of enzyme activity in chronic B lymphocytic leukemia (B-CLL) cells [2, 8,. Furthermore 5' NT expression in lymphoproliferative disorders could be related to the hypothetical maturation stage reached by the disorder, as defined by immunological marker studies [17,18].…”
mentioning
confidence: 99%